Detecção de falhas no processo de comunicação e análise dos impactos sobre a segurança de vôo pelo controle de tráfego aéreo - LIMA, Robervandro Silva de (Universidade Federal do Pará, 2021)
It is known that communication, despite the technological advances still presents numerous bottlenecks that can compromise the safety of the air traffic acted by pilot and control; and pilot and other aircraft. However, this process is more complex because it involves aspects of communication related to language, language understanding, ambiguity, uncertain reference, implicit inference, homophony, intonation, repetition (or comparison), and so on. The present dissertation aims to analyze the alternatives for detecting failures in the communication process and the impacts on flight safety by air traffic control. Thus, it should be emphasized that the objective of this work is to analyze the communication process and its failures in air traffic control and to propose devices to detect these faults in a preventive way in order to reduce the impacts on flight safety. Therefore, it is extremely important to propose a communication failure detection, reducing possible risks that can lead to air accidents. Despite this technology applied in the communication system between ground control stations, the communication model used between controllers and pilots, is still a segment that needs a lot of attention and new ways of improving the communicative process, which still has outdated characteristics and which generates negative influence of the several elements described in the communication models to be studied. Its methodology has a bibliographic nature with an experimental proposal.